Lightweight models for detection of denial‐of‐service attack in wireless sensor networks. Issue 4 (10th March 2021) - Abidoye, Ademola P.; Kabaso, Boniface
Abstract: Wireless sensor networks (WSNs) are becoming more popular in recent times due to the availability of low cost, the short transmission range of sensor nodes and their easy deployment in different application areas; however, security is crucial for WSNs due to the nature of data they transmit in most cases in their locations. Sensor nodes transmit through an open medium and due to the short communication range of each sensor node, a node may need to transmit through many hops to a final destination. Denial‐of‐service (DoS) is one of the attacks that can be launched against WSNs to prevent legitimate nodes from transmitting/receiving data packets. Developing an attack detection and countermeasure system to mitigate the effect of DoS is not an easy task. This work proposes lightweight models for DoS attack detection in WSNs. We developed different lightweight models and algorithms for the detection and elimination of DoS in WSNs and experimented the same. The performance of data delivery ratio, delay, detection rate, energy consumption, and false‐positive was carried out. The experimental results show that the proposed scheme achieved a high true‐positive detection rate, low false‐positive detection rate, energy‐efficient, and high data reliability. Numerical examples are presented to further validate the effectiveness of the proposed scheme.